(untitled) (Journal of Academic Research, 2026)
This research aimed to identify the readiness of secondary schools in Misrata to utilize virtual laboratories in chemistry teaching. To this end, the researchers adopted a descriptive survey methodology. The research population consisted of all chemistry teachers in secondary schools in Misrata, totaling 177 teachers. To achieve the research objective, a questionnaire consisting of 38 items distributed across 5 axes was used as the data collection tool. The data was then analyzed using appropriate statistical methods and the SPSS software. The research yielded the following results: - The degree of availability of the requirements for utilizing virtual laboratories in teaching chemistry in secondary schools in Misrata, according to the teachers’ responses, was moderate. - There are no statistically significant differences at the significance level (α ≤ 0.05) between chemistry teachers’ responses regarding the availability of virtual lab requirements, attributable to the variables of academic qualification and years of experience. - There are no statistically significant differences at the significance level (α ≤ 0.05) between chemistry teachers’ responses regarding the availability of requirements related to the learning environment, learners, curriculum, and virtual software, attributable to the variable of training courses. However, there are statistically significant differences in determining the availability of requirements related to the teacher, attributable to the variable of training courses, with the differences favoring teachers who have completed training courses, resulting in a mean score of 3.48.